Same As It Ever Was? Musicology Continues to Wrestle with Rock - Fast, Susan (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2000)
Popular music studies is approached from a number of disciplinary perspectives. Most recently, musicologists and music theorists have become interested in the analysis of popular music. This has sparked heated debates both within musicology and music theory, and outside it from sociologists and other cultural critics. The author traces some of that debate and argues for a popular music analysis that takes social meanings into account, using language that does not alienate those who are not professional musicians. It is argued that this is of paramount importance, since popular music is one of the most important means through which many people in the West shape their worlds.